APPROACHES TO THE STUDY OF COGNITIVE ACTIVITY OF PRIMARY SCHOOL STUDENTS - Ергалиева, Гүлжан Алгазиевна (Вестник ЗКУ, 2022)
This article discusses the theory of cognitive learning in elementary school, the structure of cognitive activity of a student, project examples of the implementation of cognitive activity of students, and their development. The characteristics of the theory of cognition, age, and psychological characteristics of younger schoolchildren, patterns, and principles of development are given. Numerous upgrades and modifications have been made to the primary school system in our nation in light of the successes of the global educational sphere at this time. The state educational standard has been updated and new requirements have been established. The educational standards define learning in the form of personal, meta-subject, and subject results, reflecting the types of activities that students should specifically master in the process of completing the initial level. The educational process is carried out based on the educational and cognitive activity of students, and based on educational and cognitive activity, the cognitive activity of students is formed. Interest in active cognitive activity develops based on understanding the social essence of education, and the need to accelerate the pace of service to society. The issues of determining the level of cognitive activity of younger schoolchildren, considering the effectiveness of ways to form readiness for project activities were highlighted. On this basis, the relevance of the study of the development of intellectual, personal qualities, and professionally significant skills of students is substantiated. This, in turn, is the result of the unity of cognitive, volitional sensory processes and motives, including cognitive interests and needs of the individual, activity, and curiosity.